2017
DOI: 10.1016/j.ijid.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Trends and characteristics of drug-resistant tuberculosis in rural Shandong, China

Abstract: Increasing MDR-TB and rates of primary MDR-TB characterize DR-TB cases in rural China. Persistent efforts need to be made among MDR-TB patients in future TB control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
4
2
Order By: Relevance
“…Analysis of 43 drug-resistant tuberculosis cases showed that females were more affected by drug-resistant tuberculosis. This finding consistent with the study conducted in China, 8 , 9 however, contrary to the study conducted in India and Brazil. 12 , 13 Our findings indicated that the majority of the cases were among people aged greater than 15 years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Analysis of 43 drug-resistant tuberculosis cases showed that females were more affected by drug-resistant tuberculosis. This finding consistent with the study conducted in China, 8 , 9 however, contrary to the study conducted in India and Brazil. 12 , 13 Our findings indicated that the majority of the cases were among people aged greater than 15 years.…”
Section: Discussionsupporting
confidence: 88%
“…This finding consistent with the study conducted in China and India. 8 , 9 , 13 This reflects the fact that most TB cases are among adults. Also, adults are more likely to have been previously exposed to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the low proportion for the study in Ethiopia might be due to the high-risk categorization of patients for DST during the study period, or the misclassification bias mentioned above or the ongoing transmissions of MDR/RR TB might have increased the proportion of primary cases in the current study. The result is also lower than the studies done in rural population of Shandong China [14] , Shenen Gibe hospital in Ethiopia [27] 70% and 36% respectively. The variation might be due to the high prevalence of MDR-TB case in Shandong china, the most economically disadvantaged region with delays in diagnosis and effective treatment of MDR TB and in Shenen Gibe hospital in Ethiopia the sample size was very small that might not detect the true proportion of the cases and the study period was also at time when GeneXpert test was being scaled up that might have increased the chance for primary MDR/RR TB case to undergo DST.…”
Section: Discussioncontrasting
confidence: 65%
“…Although there is an increasing rate of MDR/RR TB [12] , [13] , [14] , there is under detection of DR-TB in general and in new TB cases in particular due to risk categorization of presumptive TB cases to diagnose DR-TB [7] , [15] . Based on incidence of new drug resistant TB cases in terms of population, Sub Saharan Africa countries have highest rate of transmitted resistance [16] .…”
Section: Introductionmentioning
confidence: 99%